2020
DOI: 10.21608/ejhc.2020.176784
|View full text |Cite
|
Sign up to set email alerts
|

In-services Education Program for Improving Nurses' Performance Regarding Infection Control Measures in a Rural Hospital

Abstract: Nowadays, Nosocomial infection and hospital-acquired infection are a worldwide problem that increases morbidity and mortality among the hospitalized patients and surges an additional cost. Rural nurses have a paramount role in preventing infection and providing high quality of patient care. Aim: This study existed to assess the effectiveness of an in-service education program for improving nurses' performance concerning the application of infection control measures in rural hospitals. Setting: This study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The current study's findings show that in the NICU, approximately three-fourths of the nurses scored poorly on environmental cleaning activities. These findings support a study by Belal et al (2020) conducted at a small hospital in rural Egypt that revealed inadequate practices in relation to environmental cleanliness and infection control. According to Ahmed, Mohammed, and Elwasefy (2020) study in Egypt, 66% of NICU nurses had performance scores that were below average in incubator care and regular daily care.…”
Section: Discussionsupporting
confidence: 88%
“…The current study's findings show that in the NICU, approximately three-fourths of the nurses scored poorly on environmental cleaning activities. These findings support a study by Belal et al (2020) conducted at a small hospital in rural Egypt that revealed inadequate practices in relation to environmental cleanliness and infection control. According to Ahmed, Mohammed, and Elwasefy (2020) study in Egypt, 66% of NICU nurses had performance scores that were below average in incubator care and regular daily care.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, knowledge, skills, performance feedback, persistent fear of infection, and fatigue are other factors that affect nurse performance ( Alqahtani et al, 2022 ; Diana et al, 2021 ; Tesfaye & Abera, 2015 ). Therefore, it is necessary to carry out educational interventions for nurses and develop and update infection control guidelines to improve the performance of health workers, especially IPCLN, in providing services ( Belal et al, 2020 ; Spendlove, 2011 ). The in-service education intervention reported a remarkable increase in nurses’ knowledge and performance of infection control measures in the hospital ( Belal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to carry out educational interventions for nurses and develop and update infection control guidelines to improve the performance of health workers, especially IPCLN, in providing services ( Belal et al, 2020 ; Spendlove, 2011 ). The in-service education intervention reported a remarkable increase in nurses’ knowledge and performance of infection control measures in the hospital ( Belal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%